Influence of oxygen on the stabilization reaction of polyacrylonitrile fibers. Issue 3 (13th May 2012) - Xiao, Shijie; Wang, Bin; Zhao, Chun; Xu, Lianghua; Chen, Biaohua
Abstract Stabilized polyacrylonitrile (PAN) fibers pretreated under N2 and air atmospheres were prepared and their thermal behaviors were compared by differential scanning calorimetry and thermogravimetry methods. The results indicated that the subsequent stabilization reaction of PAN pretreated in air was more obvious than that in N2. In addition, the thermal stability of PAN pretreated in air is better than that in N2. The structural analysis by Fourier transform infrared spectroscopy and solid state 13C nuclear magnetic resonance implied that oxygen promoted dehydrogenation and a compact conjugated structure was formed in PAN. In addition, the CO structures were generated in air and increased gradually with temperature. The contents of oxygen in PAN fibers studied by elemental analysis corresponded with the structural evolution. Further investigation indicated that the CO structures helped dehydration and also promoted formation of the cross‐linked structures. A mechanism for structural evolution in PAN during stabilization in air was proposed. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013